EFFECTIVE CRM ENHANCEMENT STRATEGIES FOR INDIAN RETAIL MARKET - Ker-Chang Chang, Henry; Lin, Hardy; Patankar, Nilesh (International Journal of Research -GRANTHAALAYAH, 2017)
The retail sector in India is one of the fast paced moving sectors and as per the experts; retail sector market size growth is expected to USD 1.3 trillion by 2020. Among India’s most attractive features for doing business, investors rated its vast domestic market and availability of cheap labor as most appealing which made India as a most promising emerging market among Asian countries and has become Centre of attraction for investors all around the globe. Taiwan is also not behind the race. After President Tsai’s proposal of “new southbound policy”, many investors from Taiwan including Terry Gou have shown a keen interest in Indian market. Though the potential growth is immense, due to ever increasing competition retailers are always under pressure to engage their customers more efficiently than before. The purpose of this paper is to explain incorporation of RFM analysis techniques to provide key insights to the retailers. It is expected that with the proposed approach retailers and investors from India and Taiwan will be able to create customer focused sales driven strategies to create amazing shopping experience for its customers.